2015
DOI: 10.1002/ets2.12045
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Young Hispanic Dual Language Learners' Achievement: Exploring Strategies and Addressing Challenges

Abstract: pic@ets.orgCopies can be downloaded from:www.ets.org/research/picThe views expressed in this report are those of the author and do not necessarily reflect the views of the officers and trustees of Educational Testing Service. About ETSAt ETS, we advance quality and equity in education for people worldwide by creating assessments based on rigorous research. ETS serves individuals, educational institutions and government agencies by providing customized solutions for teacher certification, English language learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 183 publications
(356 reference statements)
0
8
0
Order By: Relevance
“…For example, conducting ongoing assessments of children's learning and development as a means for informing teachers' practice requires a solid grounding in child development, the content of what is being taught, and early childhood pedagogy (Buysse et al 2013;Ertle et al 2008;Ginsburg 2009;Gummer and Mandinach 2015). This is particularly critical if young children speak a home language other than English and/or are identified as having special needs (Ackerman and Tazi 2015;Wall 2011). Thus, while it may be useful to provide new staff with a single introductory training on the use of formative or summative assessments, improving their knowledge and practice related to the administration of specific assessments and/or assessment approaches likely requires an ongoing effort.…”
Section: Matching Training With Learning Goalsmentioning
confidence: 99%
“…For example, conducting ongoing assessments of children's learning and development as a means for informing teachers' practice requires a solid grounding in child development, the content of what is being taught, and early childhood pedagogy (Buysse et al 2013;Ertle et al 2008;Ginsburg 2009;Gummer and Mandinach 2015). This is particularly critical if young children speak a home language other than English and/or are identified as having special needs (Ackerman and Tazi 2015;Wall 2011). Thus, while it may be useful to provide new staff with a single introductory training on the use of formative or summative assessments, improving their knowledge and practice related to the administration of specific assessments and/or assessment approaches likely requires an ongoing effort.…”
Section: Matching Training With Learning Goalsmentioning
confidence: 99%
“…Shifts in the current political and fiscal climate have shaped the quality of the educational opportunities that exist for young learners and the early childhood workforce (Ackerman & Tazi, ). The Race to the Top–Early Learning Challenge (RTT–ELC), a discretionary grant program authorized by the U.S. Congress in 2011 and administered by the U.S. Department of Education and the U.S. Department of Health and Human Services, calls for reform in five key areas: state early learning systems, early childhood programs, the early childhood education workforce, young children's early learning and development outcomes, and the appropriate measurement of outcomes and children's progress.…”
mentioning
confidence: 99%
“…To mitigate the potential effect of language on the validity and reliability of assessments used with English learners, policy makers may allow these students to hear translations of test directions or item prompts as well as demonstrate what they know or can do in their home language (Guzman‐Orth et al, 2017; Lopez et al, 2017). However, teachers cannot be expected to be proficient in all of their students' respective home languages (Ackerman & Tazi, 2015). Not surprisingly, previous research has suggested some validity and reliability concerns when teachers serve as an assessor or observer in classrooms serving young English learners (Hanover Research, 2017; Howard et al, 2017; Lambert et al, 2015; Miller‐Bains et al, 2017; Soderberg et al, 2013).…”
Section: Assessing Young Children: Potential Validity Reliability Amentioning
confidence: 99%